'Memento Mori' : a cultura material funerária de Nova Bassano/RS - Galvan, Ana Carolina Lorenzet (2022)
Cemeteries are places of memory par excellence. The construction of these places aims to overcome the barrier of human mortality. Crosses and headstones are devices through which we can access memories and identities. We can understand these devices as heritage and material culture, realizing that they are not simple objects but have an active role and represent the concrete dimension of social relations. This remembrance practice permeated different immigrant ethnic groups, being relevant to the history of a community. We noticed a gap in the historiography regarding cemetery studies in the interior of Rio Grande do Sul. Thus, we propose to study the burial spaces in the city of Nova Bassano/RS. The municipality of the mountain region of Rio Grande do Sul received European immigrants at the end of the 19th century when it still belonged to the colony of Alfredo Chaves. New identifications emerged in these areas of mixed colonization with the encounter between diversified groups. It is possible to see the transposition of these identifications to cemeteries. The first chapter deals with the European immigration movement towards the Rio Grande do Sul, contextualizing Nova Bassano as a municipality and the identity formation in the in-between place of mixed colonization. The second chapter addresses the implementation of the cemetery project, through which burials began to take place in the cemeteries. In the same chapter, we discuss heritage, cemeteries, and tourism. In the third chapter, we relate the history and material culture through interviews, field visits, and analysis of selected elements. Our work methodology raised in consideration the approximation between material culture studied par excellence by Archeology, and History, working from material sources cataloged in field visits, elaboration of selection criteria and cataloging framework, seeking to understand the materiality of sources with the immateriality of identity construction. We also discuss the research sources and present the methodology used, questioning the conservation and the abandonment of some burial spaces, realizing that the choices regarding preservation or disposal influence the perception of the historicity of locations. This work presents contributions to the study of cemeteries in the interior through a methodological proposal of cataloging the graves and analysis in the context of material culture.